The writings of the New Testament : an interpretation - Johnson, Luke Timothy; Penner, Todd C. (Minneapolis Fortress Press, 1999)
The completely revised and updated version of Johnson's very successful introduction to the New Testament (1999) is now available with a CD-ROM that contains the entire original text with copious searching and researching features, plus hyper-links to the NRSV. This book serves as an introduction to the writings of the New Testament (NT). Its subject is a set of writings ordinarily found with another collection in the large anthology called the Bible. These writings came to birth in a specific time and place and were generated by specific causes. It may seem odd to think of the "birth" of literature, but the word is a reminder that what the reader now meets as an ancient text began as a living expression of living experience, and entered the world with a still visible parentage. - Publisher.
pt. 1: The symbolic world of the New Testament -- The Greco-Roman world -- Judaism in Palestine -- Diaspora Judaism -- pt. 2: The Christian experience -- The claims of the first Christians -- The resurrection faith -- Jesus in the memory of the church -- pt. 3: The synoptic tradition -- The Gospel of Mark -- The Gospel of Matthew -- Luke-Acts -- pt. 4: The Pauline traditions -- Paul's ministry and letters -- 1 and 2 Thessalonians -- The Corinthian correspondence -- The letter to the Galatians -- The letter to the Romans -- The letter to the Philippians -- The letter to Philemon -- The letter to the Colossians -- The letter to the Ephesians -- Pastoral letters : 1 Timothy, 2 Timothy, Titus -- pt. 5: Other canonical witnesses -- The letter to the Hebrews -- 1 Peter -- 2 Peter and Jude -- The letter of James -- pt. 6: The Johannine traditions -- The Gospel of John -- 1, 2, and 3 John -- The Book of Revelation.
Includes bibliographical references and indexes.
Keywords: Bible. -- Introductions